The Effect of Education About The Kangaroo Mother Care (KMC) Through Video Media on The Knowledge and Attitudes of Mothers Having Low Birth Weight (LBW) Babies - Christiana, Risna; Cahyati, Yanti; Putri, Laila; Widia Lestari, Meti; Wulandara, Qanita (International Journal of Advanced Multidisciplinary, 2025)
LBW is a baby born weighing less than 2500 grams. In addition to assessing weight, LBW can also be evaluated from the size of the body length and head circumference. LBW causes various problems both in the short and long term. Therefore, this incident has become a global public health problem. Kangaroo Mother Care (KMC) is a treatment for low birth weight or premature babies by making direct contact between the baby's skin and the mother's skin or skin-to-skin contact, where the mother uses her body temperature to warm the baby. The main factor in implementing the Kangaroo Mother Care (KMC) is the adequate level of knowledge possessed by the mother, which significantly increases the success of the implementation of KMC. A positive and strong attitude from the mother towards KMC is identified as a key factor for the success of the implementation of KMC. The purpose of this study was to see the effect of the Kangaroo Mother Care (KMC) Through Video Media on the Knowledge and Attitudes of Mothers Who Have Low Birth Weight (LBW) Babies. This study used a pre-experimental design. The design used in this study was a group pretest-posttest design. The sampling technique in this study was nonprobability sampling with a purposive sampling method. The results showed that there is a significant influence between the knowledge and attitudes of mothers before and after being given education about Kangaroo Mother Care (KMC).